Political and aesthetic ideas in the correspondence related to Domingos Sequeira and Vieira Portuense - Faria, Miguel Figueira de (2019)
This paper is based on the correspondence of artists Domingos António de Sequeira(1768–1837) and Francisco Vieira Portuense(1765–1805) and other epistolographic documents concerning them. In those days correspondence between Portuguese artists was scarce. The set of documents under study refers to the active and passive letters exchanged between artists and their respective patrons or liaison officers during their training period in Rome. In Sequeira’s case, I have included letters to and from his family exchanged at the end of his career.